Shaping the Shift: Unpacking Uncertainties in Change Management for Service Delivery of Selected Commercial Banks in Nairobi City County, Kenya - Rosemary Suge; Janet Muthimi (European Scientific Journal, ESJ, 2026)
The constant technological advancement has put the banking sector under heightened pressure to achieve corporate goals, boost productivity and profitability, manage operational expenses, minimize waste, and enhance service delivery. Extended periods of insufficient service delivery may be contributing factors to the decreasing customer base and performance of Kenyan commercial banks, which have not seen significant changes over the last five years. Therefore, this study focused on shaping the shift: unpacking uncertainties in change management for service delivery of selected commercial banks in Nairobi City County, Kenya. The research was underpinned by three theories, namely stakeholder theory, path-goal leadership theory, and service quality theory. A descriptive research design was employed for this study, with seven commercial banks in Kenya being selected, totaling 314 personnel working in these banks across finance, credit, marketing, and risk management departments. A simple random sampling technique was used to select respondents from each stratum, leading to a total of 176 respondents. A pilot test was undertaken by distributing 18 questionnaires to bank managers at SBM Bank. Reliability of the questionnaire was determined by using Cronbach's alpha. Data was analyzed using descriptive and inferential statistics. The results were presented using tables. The research found that there was a strong, positive, significant relationship between leadership strategy, stakeholder engagement strategy, communication strategy, planning strategy, and service delivery. The study therefore concludes that effective leadership strategies enhance employee satisfaction and engagement, leading to improved service delivery, engaging customers through feedback mechanisms, surveys, and focus groups allows banks to understand their needs and preferences, effective communication strategies foster better engagement with customers, allowing banks to understand their needs and preferences and planning strategy aids in the optimal allocation of resources, including human, financial, and technological resources. The study recommends that banks should develop systems for collecting and analyzing customer feedback to understand their needs and expectations. The banks should regularly gather feedback from customers, employees, and other stakeholders to understand their needs and expectations. The banks should recognize the various stakeholders involved, including customers, employees, regulators, and community members. The banks should conduct regular surveys and focus groups to understand customer needs, preferences, and pain points.